Financial management as an administrative function of the local school boards - Tanchuan, Antonio V. 1923-
The financial management performance of local schools boards in the Western Visayas was evaluated using participant and non-participant observations, documentary analysis of their budgets, and test-restest technique. Local school boards performed their planning, programming and budgeting functions in pursuance of predetermined goals and objectives set by them, by the educational system, and by the nation. Board decisions were in accordance with sound financial management principles, particularly where the benefit cost relationship would apply. Primary among the factors that hampered board operations are limited resources derivable from the Special Education Fund.